BEX4 upregulation alters Sertoli cell growth properties and protein expression profiles: An explanation for cadmium‐induced testicular Sertoli cell injury. Issue 7 (15th March 2017) - Yu, Wu; Yaping, Liu; Mingjun, Wu; Jie, Hao; Xiaogang, Liao; Gang, Li
Abstract: Increasing evidence has demonstrated that cadmium (Cd) may induce testicular dysfunction by targeting genes that are expressed in the testis. Here, we demonstrated that BEX4 is expressed in testis Sertoli cells, and its expression was significantly upregulated by CdCl2 treatment through activating the p38 signaling pathway. To investigate whether augmented BEX4 expression affects Sertoli cell growth and function, BEX4‐overexpressing TM4 Sertoli cells were established. Proteomics analysis identified 85 differentially expressed proteins in BEX4‐overexpressing cells. Bioinformatics analysis revealed that most of the significantly upregulated proteins had functional implications in cellular metabolic processes, whereas those that were downregulated were mostly related to cell cycle and cell communication. Therefore, the present study provides the first evidence that BEX4 upregulation induces alterations in Sertoli cell growth properties and protein expression profiles, which may be an explanation for Cd‐induced testicular Sertoli cell injury.